CSR DAN CITRA PERUSAHAAN - Yosa Vega Prasiska; Bunga Pertiwi; Yosi Rizky Nabila; Kristin Indah; Diani Safitr (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2017)
This research aims to know the influence of Corporate Social Responsibility towards the company's image in the community around company PT Pandatex measured variables of the Corporate Social Responsibility of Commu nity Support, Environment and Non teritorial. Operation. It is hoped the information obtained from this research can be used by companies to improve the activities and the quality of Corporate Social Responsibility so that more can improve the corporate image in the future. This research using quantitative methods by conducting a survey of about PT Pandatex. This research data analysis using multiple linear analysis and the conclusion that the gets Community Support and Environment does not have significant influence towards corporate image whereas Non u.s. Operation to the image of the company. As for the details of the value of the variable third as follows: Community Support registration -1,298 Environment of 0.385 and Non teritorial Operation 7,381. Keywords: Corporate Social Responsibility (CSR), corporate image, Community Support, the Environment and Non teritorial. Operation